Immune response of chicken gut to natural colonization by gut microflora and to Salmonella enterica serovar enteritidis infection - Crhanova, Magdalena; Hradecka, Helena; Faldynova, Marcela; Matulova, Marta; Havlickova, Hana; Sisak, Frantisek; Rychlik, Ivan (Infection and immunity, 2011)
In commercial poultry production, there is a lack of natural flora providers since chickens are hatched in the clean environment of a hatchery. Events occurring soon after hatching are therefore of particular importance, and that is why we were interested in the development of the gut microbial community, the immune response to natural microbial colonization, and the response to Salmonella enterica serovar Enteritidis infection as a function of chicken age. The complexity of chicken gut microbiota gradually increased from day 1 to day 19 of life and consisted of Proteobacteria and Firmicutes. For the first 3 days of life, chicken cecum was protected by increased expression of chicken β-defensins (i.e., gallinacins 1, 2, 4, and 6), expression of which dropped from day 4 of life. On the other hand, a transient increase in interleukin-8 (IL-8) and IL-17 expression could be observed in chicken cecum on day 4 of life, indicating physiological inflammation and maturation of the gut immune system. In agreement, the response of chickens infected with S. Enteritidis on days 1, 4, and 16 of life shifted from Th1 (characterized mainly by induction of gamma interferon [IFN-γ] and inducible nitric oxide synthase [iNOS]), observed in younger chickens, to Th17, observed in 16-day-old chickens (characterized mainly by IL-17 induction). Active modification of chicken gut microbiota in the future may accelerate or potentiate the maturation of the gut immune system and increase its resistance to infection with different pathogens.
Keywords: nemoci drůbeže; Th1 buňky; Immunity, Innate; interleukin-17; salmonelová infekce u zvířat; Chickens; Salmonella enteritidis; Th17 Cells; Salmonella Infections, Animal; enteritida; cytokiny; Interleukin-8; RNA ribozomální 16S; stárnutí; ELISA; Cecum; interleukin-8; Interleukin-17; cékum; zvířata; Aging; RNA, Ribosomal, 16S; Enzyme-Linked Immunosorbent Assay; beta-Defensins; beta-defensiny; Proteobacteria; Poultry Diseases; kur domácí; buňky Th17; polymerázová řetězová reakce; Cytokines; Th1 Cells; Polymerase Chain Reaction; Enteritis; Animals; Gastrointestinal Tract; přirozená imunita; gastrointestinální trakt